Benthic diatom diversity in a turbid brackish lagoon of the Baltic Sea. Issue 2 (4th March 2023) - Kuriyama, Kana; Heesch, Svenja; Karsten, Ulf; Schumann, Rhena
ABSTRACT: The Darß-Zingst Bodden Chain is a tide-less shallow lagoon at the Southern Baltic coast. It was and is studied in almost all hydrological, biogeochemical as well as floristic and faunistic aspects. Benthic diatoms were studied using light and scanning electron microscopy (SEM) in the early 1970s and one sampling site was now revisited. A total of 103 diatom taxa were recorded in sediment and on macrophyte samples collected between 2015 and 2019. In the sediment samples, epipsammic diatoms accounted for almost 90% of the total valve counts. In the 1970s, only three epipsammic species were observed, while we recorded a total of 27 epipsammic taxa, most of which were very small (<12 µm). Since those earlier studies, many of these species have been newly described or transferred from other genera. Moreover, small diatoms may have been misidentified, overlooked or counted as important. This study emphasizes, in addition, the need to combine light microscopy with electron microscopy to allow the unambiguous identification also of small entities, and to reach a comprehensive overview over the diatom flora present in different benthic habitats.